SLAP tears and return to sport and work: current concepts. Issue 4 (11th March 2021) - LeVasseur, Matthew R; Mancini, Michael R; Hawthorne, Benjamin C; Romeo, Anthony A; Calvo, Emilio; Mazzocca, Augustus D
Abstract : Superior labrum, anterior and posterior (SLAP) lesions are common and identified in up to 26% of shoulder arthroscopies, with the greatest risk factor appearing to be overhead sporting activities. Symptomatic patients are treated with physical therapy and activity modification. However, after the failure of non-operative measures or when activity modification is precluded by athletic demands, SLAP tears have been managed with debridement, repair, biceps tenodesis or biceps tenotomy. Recently, there have been noticeable trends in the operative management of SLAP lesions with older patients receiving biceps tenodesis and younger patients undergoing SLAP repair, largely with suture anchors. For overhead athletes, particularly baseball players, SLAP lesions remain a difficult pathology to manage secondary to concomitant pathologies and unpredictable rates of return to play. As a consequence, the most appropriate surgical option in elite throwers is controversial. The objective of this current concepts review is to discuss the anatomy, mechanism of injury, presentation, diagnosis and treatment options of SLAP lesions and to present current literature on outcomes affecting return to sport and work.